Effects of Emericella nidulans and Eurotium sp. in Controlling Fusarium Wilt Caused by Fusarium oxysporum f. sp. lycopersici - Sibounnavong, Phonesavard; Sibounnavong, Phoutthasone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The effect of Emericella nidulans and Eurotium sp. to control Fusarium oxysporum f. sp. lycopersici, the objectives of this research to testing antifungal of Emericella nidulans and Eurotium against Fusarium oxysporum f. sp. lycopersici by bi-culture method and using crude extracts to inhibited by food poisoned techniques, the experimental design using Completely Randomized Design with 4 replications. Tested Emericella nidulans and Eurotium sp. against mycelial growth and spore production of Fusarium oxysporum f. sp. lycopersici by bi-culture and crude extracts method. Bi-culture test showed that Emericella nidulans and Eurotium sp. inhibited mycelial growth and spore production of Fusarium oxysporum f. sp. lycopersici at 51.80%, 52.06% and 43.78%, 62.27% respectively. Crude extracts were extracted from Emericella nidulans and Eurotium sp. with hexane, EtOAc and MeOH, crude hexane at 1000 µg/ml gave the best inhibited mycelial growth and spore production of Fusarium oxysporum f. sp. lycopersici, the effective dose (ED50) were 1.28 µg/ml and 0.126 µg/ml respectively.